2001
DOI: 10.1007/bf03404946
|View full text |Cite
|
Sign up to set email alerts
|

Factors Important in Promoting Cervical Cancer Screening among Canadian Women: Findings from the 1996–97 National Population Health Survey (NPHS)

Abstract: Approximately 1,450 new cases and 430 deaths from cervical cancer were estimated to occur among Canadian women during 2000, resulting in an estimated incidence rate of 8.4 per 100,000 women. 1 Observed declines in cervical cancer incidence and mortality rates in previous years are largely attributed to the widespread adoption of Pap screening. 1 Current Canadian guidelines recommend women receive annual Pap tests once sexually active or at age 18 with a reduction in screening frequency to every three years aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
111
2
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(134 citation statements)
references
References 22 publications
20
111
2
1
Order By: Relevance
“…Our analyses of factors associated with inconsistent ever/never responses indicate that women reporting ever having had a mammogram at baseline but never use at follow-up exhibited many of the sociodemographic and health behaviour characteristics (e.g., lower income, outside age groups targeted for screening, non-users of Pap screening and hormone replacement therapy) commonly observed among non-participants in mammography screening in previous studies [31-38]. Such findings provide support for the assumption that the 1994–95 response of ever use is more likely erroneous.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Our analyses of factors associated with inconsistent ever/never responses indicate that women reporting ever having had a mammogram at baseline but never use at follow-up exhibited many of the sociodemographic and health behaviour characteristics (e.g., lower income, outside age groups targeted for screening, non-users of Pap screening and hormone replacement therapy) commonly observed among non-participants in mammography screening in previous studies [31-38]. Such findings provide support for the assumption that the 1994–95 response of ever use is more likely erroneous.…”
Section: Discussionmentioning
confidence: 75%
“…Additional factors (e.g. being born in an Asian country) previously associated with non-use of mammography [31,33] also showed a positive association with providing an inconsistent response; however, small numbers resulted in high variability once clustering and stratification were taken into account and precluded further analysis of this variable.…”
Section: Discussionmentioning
confidence: 99%
“…As noted earlier, one of our goals in designing the survey was to determine which factors were most important in influencing individuals’ decisions to be screened. We used logistic regression analysis of data collected in our survey to test whether the following individual-level factors, identified in earlier studies, were associated with the likelihood of future screening in our study population: physician recommendation, 2022 insurance status, 21,2325 past screening behavior, 22 age, 21,26 race, 26,27 education, 26 and income. 26,27 Furthermore, we tested whether learning about an early- or late-stage breast cancer diagnosis in a woman who had or had not been regularly screened within the past year affected a respondent’s future likelihood of being screened.…”
Section: Methodsmentioning
confidence: 99%
“…Studies identified demographic (Zapka et al, 1989), geographical (Lerman et al, 1990), socio-economic factors (Zapka et al, 1989, Katz and Hofer, 1994, Maxwell et al, 2001) and psychological factors (Zapka et al, 1989, Lerman et al, 1990) contributing to variation in participation in breast cancer screening. For example, less education, minority ethnicities, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies relied on self-reported data (Zapka et al, 1989, Lerman et al, 1990, Katz and Hofer, 1994, Maxwell et al, 2001, McDonald and Sherman, 2010, Tang et al, 2000) and examined initial rescreening only (Song and Fletcher, 1998, Barr et al, 2001, Bobo et al, 2004, Calvocoressi et al, 2005, Fox et al, 2004) or first and second follow-up (Rauscher et al, 2005, Bancej et al, 2005) only, without considering initial screening or retention over a longer period of time. Some existing studies have used administrative data on individuals participating in screening programs to study compliance with guidelines (Kiran et al, 2014, Corkum et al, 2014, Vigod et al, 2011) but use of Canadian administrative data has been limited (Bancej et al, 2005).…”
Section: Introductionmentioning
confidence: 99%